Catalyst slurry containing carboxyl porphyrin as well as preparation method and application of catalyst slurry
By using a catalyst slurry containing carboxyporphyrin in a proton exchange membrane fuel cell, the activity of the platinum-based catalyst is stimulated and the mass transfer efficiency is improved, and the problems of high cost and insufficient mass transfer efficiency of platinum-based catalysts in existing fuel cells are solved, and higher power density and stability are achieved.
Patent Information
- Application Number
- CN202411714562.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-14
AI Technical Summary
The existing proton exchange membrane fuel cells (PEMFCs) have poor power density and stability due to the high cost of platinum-based catalysts, scarcity of resources and insufficient mass transfer efficiency, especially under low Pt load conditions.
A catalyst slurry containing carboxyporphyrin is prepared by incorporating carboxyporphyrin compounds to stimulate the catalytic activity of the Pt catalyst and improve the mass transfer efficiency in fuel cells. The slurry includes carboxyporphyrin compounds, platinum-based catalysts, perfluorosulfonic acid electrolytes, water and alcohols, and is prepared by ultrasonic dispersion technology.
The dual-effect synergy effect is achieved, which enhances the catalytic activity and proton conductivity of the catalyst, reduces the toxicity of the active site, significantly improves the power density and stability of the fuel cell, and reduces manufacturing costs.
Smart Images

Figure CN119627123A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of proton exchange membrane fuel cells, and in particular to a catalyst slurry containing carboxyl porphyrin, a preparation method and application thereof, and specifically to a catalyst slurry containing carboxyl porphyrin, a preparation method and application thereof, a cathode catalyst layer, a proton membrane assembly and a proton membrane assembly. Background Art
[0002] Fuel cells are devices that convert chemical energy directly into electrical energy. Due to their high efficiency, low emissions and excellent environmental protection characteristics, they are widely regarded as an important part of modern energy technology. In particular, proton exchange membrane fuel cells (PEMFCs), with their advantages of fast start-up and high power density, have shown great application potential in portable devices, transportation and fixed power applications. PEMFCs are mainly composed of proton exchange membranes, catalyst layers, gas diffusion layers and other parts. The catalyst is particularly critical in fuel cells. It is located between the electrodes and the proton exchange membrane and is mainly responsible for the oxidation reaction of hydrogen and the reduction reaction of oxygen, effectively accelerating the reaction process and improving the efficiency of the battery.
[0003] Platinum (Pt)-based catalysts have become one of the most commonly used catalyst materials in proton exchange membrane fuel cells (PEMFCs) due to their excellent electrochemical activity and stability. In PEMFCs, the main role of Pt is to catalyze the oxidation reaction of hydrogen and the reduction reaction of oxygen, ensuring that the fuel cell still has high reactivity under low temperature conditions. In addition, Pt-based catalysts have good corrosion resistance and can operate stably for a long time under acidic conditions. However, due to the limited catalytic activity of Pt and the insufficient mass transfer efficiency of the Pt-based membrane electrode assembly (MEA), current PEMFCs rely heavily on high Pt loading to achieve the required power density. That is, the high cost and resource scarcity of Pt significantly increase the manufacturing cost of PEMFCs, limiting the economic feasibility of their large-scale application.
[0004] At the same time, platinum-based catalysts face other technical bottlenecks in practical applications. First, Pt-based MEAs have always faced major challenges related to low mass transfer efficiency, especially the slow transfer of protons and oxygen within the three-phase interface of the catalyst layer, which in turn leads to unsatisfactory power density and stability of PEMFC, especially under low Pt loading conditions. That is, the intrinsic activity of fuel cell catalysts can be significantly reduced by insufficient mass transfer efficiency in MEAs. Second, Pt nanoparticles tend to aggregate or dissolve at high potentials, which not only reduces the active surface area of the catalyst but also leads to the degradation of fuel cell performance.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The purpose of the present invention is to provide a catalyst slurry containing carboxyl porphyrin and its preparation method and application. The catalyst slurry is doped with carboxyl porphyrin compounds to stimulate the catalytic activity of the Pt catalyst and improve the mass transfer efficiency in the fuel cell, thereby providing a universal and effective method for significantly improving the battery performance in the field of renewable energy.
[0007] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0008] In a first aspect, the present invention provides a carboxyl porphyrin-containing catalyst slurry, wherein the carboxyl porphyrin-containing catalyst slurry comprises: a carboxyl porphyrin compound, a platinum-based catalyst, a perfluorosulfonic acid electrolyte, water and alcohol.
[0009] Preferably, the mass ratio of the carboxyl porphyrin compound to the perfluorosulfonic acid electrolyte is 1:(1-600), preferably 1:(50-600).
[0010] Preferably, the carboxyporphyrin compound includes any one of dicarboxyprotoporphyrin, dicarboxymetalloporphyrin, tetracarboxyphenylporphyrin or tetracarboxyphenylmetalloporphyrin, or a combination of at least two thereof.
[0011] Preferably, the structural formula of the dicarboxy protoporphyrin is as shown in Formula I below.
[0012]
[0013] Preferably, the structural formula of the dicarboxymetal protoporphyrin is as shown in Formula II below:
[0014]
[0015] Wherein, M is selected from any one of iron, cobalt, nickel, copper or zinc or a combination of at least two thereof. Preferably, the structural formula of the tetracarboxylphenylporphyrin is as shown in the following formula III:
[0016]
[0017] Preferably, the structural formula of the tetracarboxyphenyl metalloporphyrin is as shown in the following formula IV:
[0018]
[0019] Wherein, M is selected from any one of iron, cobalt, nickel, copper or zinc, or a combination of at least two thereof.
[0020] Preferably, the platinum-based catalyst includes any one of Pt / C, PtCo / C, PtFe / C, PtNi / C or PtCu / C, or a combination of at least two thereof.
[0021] Preferably, the mass percentage of platinum in the platinum-based catalyst is 10-60%.
[0022] Preferably, the alcohol is selected from any one of methanol, ethanol, n-propanol, isopropanol, n-butanol or tert-butanol, or a combination of at least two thereof, preferably n-propanol.
[0023] Preferably, the mass ratio of the platinum-based catalyst, the carboxyl porphyrin compound, the perfluorosulfonic acid electrolyte, water and alcohol is 1:(0.01-10):(1-50):(10-100):(50-500).
[0024] In a second aspect, the present invention provides a method for preparing a catalyst slurry containing carboxyl porphyrin as described in the first aspect, the preparation method comprising the following steps:
[0025] (1) mixing a carboxyporphyrin compound, a perfluorosulfonic acid electrolyte and an alcohol, and dispersing the mixture once to obtain a dispersion;
[0026] (2) The platinum-based catalyst, water, alcohol and dispersion liquid are mixed and dispersed twice to obtain the catalyst slurry containing carboxyl porphyrin.
[0027] Preferably, in step (1), the mass ratio of the carboxyporphyrin compound, the perfluorosulfonic acid electrolyte and the alcohol is 1:(1-600):(100-1000).
[0028] Preferably, in step (1), the primary dispersion is ultrasonic dispersion, the power of the primary dispersion is 20 to 300 W, and the time of the primary dispersion is 20 to 60 min.
[0029] Preferably, in step (2), the mass ratio of the platinum-based catalyst, water, alcohol and dispersion is 1:(10-100):(50-200):(1-10).
[0030] Preferably, in step (2), the secondary dispersion is ultrasonic dispersion, the power of the secondary dispersion is 20 to 300 W, and the time of the secondary dispersion is 20 to 60 min.
[0031] In a third aspect, the present invention provides a use of the catalyst slurry containing carboxyl porphyrin as described in the first aspect in the preparation of a fuel cell.
[0032] In a fourth aspect, the present invention provides a cathode catalyst layer, comprising a catalyst layer formed by the catalyst slurry containing carboxyl porphyrin as described in the first aspect.
[0033] In a fifth aspect, the present invention provides a proton membrane assembly, the proton membrane assembly comprising: a proton exchange membrane and a cathode catalyst layer and an anode catalyst layer located on both sides of the proton exchange membrane;
[0034] Wherein, the cathode catalyst layer includes the cathode catalyst layer as described in the fourth aspect.
[0035] In a sixth aspect, the present invention provides a fuel cell, the fuel cell comprising a proton membrane assembly;
[0036] Wherein, the proton membrane assembly includes the proton membrane assembly as described in the fifth aspect.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] (1) In the preparation of fuel cell catalysts assisted by carboxyl porphyrin compounds provided by the present invention, a dual-effect synergistic effect is achieved. The metal center in the metal porphyrin can enhance the catalytic activity of the catalyst by strongly adsorbing oxygen.
[0039] (2) The catalyst of the present invention starts from regulating the interaction between the catalyst and the surface of the perfluorosulfonic acid electrolyte and enhancing the proton conductivity. By adding carboxyl metal porphyrin to interact with the perfluorosulfonic acid electrolyte, the active site poisoning is reduced and the proton transport of the catalytic layer is improved.
[0040] (3) The method for preparing a carboxylporphyrin-assisted fuel cell catalyst provided by the present invention is simple, easy to operate, low in cost, has universal applicability and great commercial potential, and has broad prospects for promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0042] Figure 1 This is a scanning electron microscope image of the catalyst layer formed by the catalyst slurry containing carboxyl porphyrin provided in Example 8.
[0043] Figure 2 This is a scanning electron microscope image of the catalyst layer formed by the catalyst slurry provided in Comparative Example 1.
[0044] Figure 3 It is a comparison diagram of polarization curves and power density curves measured for fuel cells containing membrane electrodes having catalyst layers formed by the catalyst slurries of Example 8 and Comparative Example 1.
[0045] Figure 4A This is a comparison diagram of polarization curves measured for fuel cells containing membrane electrodes having catalyst layers formed by the catalyst slurries of Example 8 and Comparative Example 1.
[0046] Figure 4B The mass activity comparison diagram of the fuel cell containing the membrane electrode having the catalyst layer formed by the catalyst slurry of Example 8 and Comparative Example 1 is measured.
[0047] Figure 5 It is a comparison diagram of polarization curves and power density curves of fuel cells containing membrane electrodes having catalyst layers formed by the catalyst slurries of Examples 5 to 8.
[0048] Fig. 6A The diagram is a comparison of polarization curves measured for a fuel cell containing a membrane electrode having a catalyst layer formed by the catalyst slurry of Examples 5 to 7.
[0049] Figure 6B The graph is a comparison of the mass activities of the fuel cells of the membrane electrodes containing the catalyst layers formed by the catalyst slurries of Examples 5 to 7.
[0050] Figure 7 The fuel cell of the membrane electrode containing the catalyst layer formed by the catalyst slurry of Example 8 and Comparative Example 1 was subjected to 5A cm -2 The electrochemical impedance comparison chart below.
[0051] Figure 8 The CV curves at 20% RH and 100% RH in a fuel cell of a membrane electrode having a catalyst layer formed of the catalyst slurry of Comparative Example 1 are shown.
[0052] Fig. 9 The CV curves of the fuel cell membrane electrode having the catalyst layer formed by the catalyst slurry of Example 8 at 20% RH and 100% RH are shown.
[0053] Fig.10 This is a comparison chart of the electrochemical active areas in the membrane electrode fuel cell of the catalyst layer formed by the catalyst slurry of Example 8 and Comparative Example 1.
[0054] Fig.11 Proton conductivity of a fuel cell membrane electrode having a catalyst layer formed of the catalyst slurry of Example 8 and Comparative Example 1 at a relative humidity of 100% and a temperature of 50 to 80°C.
[0055] Fig.12 This is the in-situ infrared spectrum of Comparative Example 1.
[0056] Fig.13 This is the in-situ infrared spectrum of Example 8. DETAILED DESCRIPTION
[0057] Unless otherwise defined herein, scientific and technical terms used in conjunction with the present invention shall have the meanings commonly understood by those of ordinary skill in the art. The meaning and scope of the terms should be clear, however, in the case of any potential ambiguity, the definitions provided herein take precedence over any dictionary or external definitions. In this application, unless otherwise stated, the use of "or" means "and / or". In addition, the use of the term "including" and other forms is non-limiting.
[0058] It should be noted that specific details are described in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in a variety of other ways different from those described herein, and those skilled in the art can make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0059] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0060] In a first aspect, the present invention provides a carboxyl porphyrin-containing catalyst slurry, wherein the carboxyl porphyrin-containing catalyst slurry comprises: a carboxyl porphyrin compound, a platinum-based catalyst, a perfluorosulfonic acid electrolyte, water and alcohol.
[0061] In the present invention, a carboxyl-containing porphyrin compound is added to the catalyst slurry to stimulate the catalytic activity of the platinum-based catalyst and improve the mass transfer efficiency in the fuel cell. Specifically, the carboxyl porphyrin compound has a proton transfer effect, and the carboxyl group can not only react with the surface of the platinum-based catalyst, but also improve the proton transfer of the catalyst layer. In addition, the carboxyl porphyrin compound also interacts with the sulfonic acid group in the electrolyte, and the carboxyl group can weaken the poisoning effect of the sulfonic acid group on the platinum catalyst, thereby maintaining the high activity of the platinum catalyst, while accelerating proton transfer and improving the overall fuel cell performance.
[0062] As an optional embodiment of the present invention, the mass ratio of the carboxyl porphyrin compound to the perfluorosulfonic acid electrolyte is 1:(1-600), for example, it can be 1:1, 1:2, 1:4, 1:6, 1:8, 1:10, 1:15, 1:20, 1:25, 1:30, 1:35, 1:40, 1:45, 1:50, 1:60, 1:80, 1:100, 1:120, 1:140, 1:160, 1:180, 1:200, 1:220, 1:240, 1:260, 1:280, 1:300, 1:320, 1:340, 1:360, 1:380, 1:400, 1:450, 1:500, 1:550, 1:600, etc., preferably 1:(300-600).
[0063] As an optional embodiment of the present invention, the carboxyl porphyrin compound includes any one of dicarboxy protoporphyrin, dicarboxy metal protoporphyrin, tetracarboxy phenyl porphyrin or tetracarboxy phenyl metal porphyrin, or a combination of at least two thereof.
[0064] As a preferred embodiment of the present invention, the carboxyporphyrin compound is dicarboxymetal protoporphyrin and / or tetracarboxyphenylmetal porphyrin.
[0065] In the present invention, the carboxyl porphyrin compound is preferably a metal-containing carboxyl porphyrin compound, thereby achieving the dual-effect synergistic effect of metal porphyrin oxygen adsorption effect and carboxyl proton transfer effect; wherein, carboxyl metal porphyrin oxygen adsorption effect: the metal center in the metal porphyrin can increase the adsorption of oxygen, thereby enhancing the catalytic activity of the catalyst. This effect can improve the kinetics of ORR, allowing the fuel cell to achieve a higher reaction rate at a lower overpotential. And the proton transfer effect: the carboxyl group can not only act on the surface of the platinum-based catalyst, but also improve the proton transfer of the catalyst layer. In addition, by interacting with the sulfonic acid group in the electrolyte, the carboxyl group can weaken the poisoning effect of the sulfonic acid group on the platinum catalyst.
[0066] As a preferred embodiment of the present invention, the structural formula of the dicarboxy protoporphyrin is shown in Formula I below:
[0067]
[0068] As a preferred embodiment of the present invention, the structural formula of the dicarboxymetal protoporphyrin is shown in the following formula II:
[0069]
[0070] Wherein, M is selected from any one of iron, cobalt, nickel, copper or zinc, or a combination of at least two thereof.
[0071] As a preferred embodiment of the present invention, the structural formula of the tetracarboxyphenylporphyrin is shown in the following formula III:
[0072]
[0073] As a preferred embodiment of the present invention, the structural formula of the tetracarboxyphenyl metalloporphyrin is shown in the following formula IV:
[0074]
[0075] Wherein, M is selected from any one of iron, cobalt, nickel, copper or zinc, or a combination of at least two thereof.
[0076] As a preferred embodiment of the present invention, the platinum-based catalyst includes any one of Pt / C, PtCo / C, PtFe / C, PtNi / C or PtCu / C, or a combination of at least two thereof.
[0077] As a preferred embodiment of the present invention, the mass percentage of platinum in the platinum-based catalyst is 10-60%, for example, it can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, etc.
[0078] As a preferred embodiment of the present invention, the perfluorosulfonic acid electrolyte is a perfluororesin containing a sulfonic acid group.
[0079] As a preferred embodiment of the present invention, the perfluorosulfonic acid electrolyte is selected from any one of Nafion, Flemion, Aquivion or Aciplex.
[0080] As a preferred embodiment of the present invention, the perfluorosulfonic acid electrolyte is selected from any one of D2020, D520, D1035, D1050 or Nafion LXH.
[0081] As a preferred embodiment of the present invention, the alcohol is selected from any one of methanol, ethanol, n-propanol, isopropanol, n-butanol or tert-butanol, or a combination of at least two thereof, preferably n-propanol.
[0082] As a preferred embodiment of the present invention, the mass ratio of the platinum-based catalyst, the carboxyl porphyrin compound, the perfluorosulfonic acid electrolyte, water and alcohol is 1:(0.01-10):(1-50):(10-100):(50-500);
[0083] Here, “0.01-10” can be, for example, 0.01, 0.02, 0.05, 0.1, 0.2, 0.3, 0.4, 5, 6, 7, 10, etc.;
[0084] Here, “1-50” can be, for example, 1, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, etc.;
[0085] Here, “10-100” can be, for example, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, etc.;
[0086] Here, “50-500” can be, for example, 50, 80, 100, 120, 150, 180, 200, 220, 250, 280, 300, 320, 350, 380, 400, 420, 450, 480, 500, etc.
[0087] In a second aspect, the present invention provides a method for preparing a catalyst slurry containing carboxyl porphyrin as described in the first aspect, the preparation method comprising the following steps:
[0088] (1) mixing a carboxyporphyrin compound, a perfluorosulfonic acid electrolyte and an alcohol, and dispersing the mixture once to obtain a dispersion;
[0089] (2) The platinum-based catalyst, water, alcohol and dispersion liquid are mixed and dispersed twice to obtain the catalyst slurry containing carboxyl porphyrin.
[0090] It should be noted that the currently widely used method for preparing fuel cell catalyst slurry is to directly mix and ultrasonically disperse the catalyst, perfluorosulfonic acid electrolyte, deionized water and organic solvent. This will cause the catalyst to be coated with the electrolyte, poisoning some active sites to a certain extent, resulting in a denser catalytic layer, affecting local oxygen transport and failing to expose more active sites. In addition, there are also certain limitations on proton conduction in the catalytic layer.
[0091] Based on this, in the preparation process of the catalyst slurry containing carboxyl porphyrin of the present invention, the carboxyl porphyrin compound is first introduced into the catalyst layer, the carboxyl group is used to interact with the sulfonic acid group of the electrolyte, and then it is contacted with the platinum-based catalyst, which can effectively reduce the poisoning of the sulfonic acid group to the platinum-based catalyst, and the carboxyl porphyrin and / or carboxyl metal porphyrin rich in carboxyl groups and active sites optimizes the enrichment of water on the catalyst at the reaction interface and constructs an efficient proton transmission channel. In addition, the metal center in the carboxyl metal porphyrin can better improve the adsorption of oxygen, thereby enhancing the catalytic activity of the catalyst. At the same time, the present invention finds that the preparation process of the catalyst slurry containing carboxyl porphyrin is simple, easy to operate, and low in cost, which is very conducive to promoting PEMFC technology to move towards higher commercial application standards.
[0092] As a preferred embodiment of the present invention, in step (1), the mass ratio of the carboxyporphyrin compound, the perfluorosulfonic acid electrolyte and the alcohol is 1:(1-600):(100-1000);
[0093] Here, “1-600” may be, for example, 1, 50, 100, 150, 200, 250, 300, 350, 400, 450, 500, 550, 600, etc.;
[0094] Among them, “100-1000)” can be, for example, 150, 200, 250, 300, 350, 400, 450, 500, 550, 600, 650, 700, 750, 800, 850, 900, 950, 1000, etc.
[0095] As a preferred embodiment of the present invention, in step (1), the primary dispersion is ultrasonic dispersion, the power of the primary dispersion is 20 to 300 W, for example, 20 W, 40 W, 60 W, 80 W, 100 W, 120 W, 140 W, 160 W, 180 W, 200 W, 220 W, 240 W, 260 W, 280 W, 300 W, etc., and the time of the primary dispersion is 20 to 60 min, for example, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min, etc.
[0096] As a preferred embodiment of the present invention, in step (2), the mass ratio of the platinum-based catalyst, water, alcohol and dispersion is 1:(10-100):(50-200):(1-10);
[0097] Here, “10-100” can be, for example, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, etc.;
[0098] Herein, “50-200” may be, for example, 50, 60, 70, 80, 90, 100, 120, 140, 150, 160, 180, 200, etc.;
[0099] Here, “1-10” can be, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, etc.
[0100] As a preferred embodiment of the present invention, in step (2), the secondary dispersion is ultrasonic dispersion, the power of the secondary dispersion is 20-300 W, for example, 20 W, 40 W, 60 W, 80 W, 100 W, 120 W, 140 W, 160 W, 180 W, 200 W, 220 W, 240 W, 260 W, 280 W, 300 W, etc., and the time of the secondary dispersion is 20-60 min, for example, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min, etc.
[0101] In a third aspect, the present invention provides a use of the catalyst slurry containing carboxyl porphyrin as described in the first aspect in the preparation of a fuel cell.
[0102] In a fourth aspect, the present invention provides a cathode catalyst layer, comprising a catalyst layer formed by the catalyst slurry containing carboxyl porphyrin as described in the first aspect.
[0103] In a fifth aspect, the present invention provides a proton membrane assembly, the proton membrane assembly comprising: a proton exchange membrane and a cathode catalyst layer and an anode catalyst layer located on both sides of the proton exchange membrane;
[0104] Wherein, the cathode catalyst layer includes the cathode catalyst layer as described in the fourth aspect.
[0105] In a sixth aspect, the present invention provides a fuel cell, the fuel cell comprising a proton membrane assembly;
[0106] Wherein, the proton membrane assembly includes the proton membrane assembly as described in the fifth aspect.
[0107] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.
[0108] The structural formula of the porphyrin compound added in the following examples is as follows:
[0109]
[0110]
[0111]
[0112] Example 1
[0113] This embodiment provides a carboxyl porphyrin-containing catalyst slurry, and the carboxyl porphyrin-containing catalyst slurry is prepared by the following steps:
[0114] S1, weighing 4.0 mg of tetracarboxylphenylporphyrin iron, 0.6 g of Nafion (5 wt%) resin solution (specific model: D520) and 4.0 g of isopropanol, and mixing them, and ultrasonically dispersing them at a power of 100 W for 40 min to obtain a dispersion;
[0115] S2. Weigh 20 mg of a Pt / C catalyst having a Pt content of 40%, add 0.4 g of deionized water, 2.0 g of isopropanol and 0.2 g of the dispersion prepared in S1, and disperse the mixture under ultrasonic conditions at a power of 100 W for 60 min to obtain the catalyst slurry containing carboxyl porphyrin.
[0116] Example 2
[0117] This embodiment provides a carboxyl porphyrin-containing catalyst slurry, and the carboxyl porphyrin-containing catalyst slurry is prepared by the following steps:
[0118] S1, weighing 15.0 mg of tetracarboxylphenylporphyrin iron, 0.6 g of Nafion (5 wt%) resin solution (specific model: D520) and 4.0 g of isopropanol, and mixing them, and ultrasonically dispersing them at a power of 100 W for 40 min to obtain a dispersion;
[0119] S2. Weigh 20 mg of a Pt / C catalyst having a Pt content of 40%, add 0.4 g of deionized water, 2.0 g of isopropanol and 0.2 g of the dispersion prepared in S1, and disperse the mixture under ultrasonic conditions at a power of 100 W for 60 min to obtain the catalyst slurry containing carboxyl porphyrin.
[0120] Example 3
[0121] This embodiment provides a carboxyl porphyrin-containing catalyst slurry, and the carboxyl porphyrin-containing catalyst slurry is prepared by the following steps:
[0122] S1, weighing 30.0 mg of tetracarboxylphenylporphyrin iron, 0.6 g of Nafion (5 wt%) resin solution (specific model: D520) and 4.0 g of isopropanol, and mixing them, and ultrasonically dispersing them at a power of 100 W for 40 min to obtain a dispersion;
[0123] S2. Weigh 20 mg of a Pt / C catalyst having a Pt content of 40%, add 0.4 g of deionized water, 2.0 g of isopropanol and 0.2 g of the dispersion prepared in S1, and disperse the mixture under ultrasonic conditions at a power of 100 W for 60 min to obtain the catalyst slurry containing carboxyl porphyrin.
[0124] Example 4
[0125] This embodiment provides a carboxyl porphyrin-containing catalyst slurry, and the carboxyl porphyrin-containing catalyst slurry is prepared by the following steps:
[0126] S1, weighing 4.0 mg of tetracarboxylphenylporphyrin cobalt, 0.6 g of Nafion (5 wt%) resin solution (specific model: D520) and 4.0 g of isopropanol, and mixing them, and ultrasonically dispersing them at a power of 100 W for 40 min to obtain a dispersion;
[0127] S2. Weigh 20 mg of a Pt / C catalyst having a Pt content of 40%, add 0.4 g of deionized water, 2.0 g of isopropanol and 0.2 g of the dispersion prepared in S1, and disperse the mixture under ultrasonic conditions at a power of 100 W for 60 min to obtain the catalyst slurry containing carboxyl porphyrin.
[0128] Example 5
[0129] This embodiment provides a carboxyl porphyrin-containing catalyst slurry, and the carboxyl porphyrin-containing catalyst slurry is prepared by the following steps:
[0130] S1, weighing 4.0 mg of dicarboxy protoporphyrin, 0.6 g of Nafion (5 wt%) resin solution (specific model: D520) and 4.0 g of isopropanol, and mixing them, and ultrasonically dispersing them at a power of 100 W for 40 min to obtain a dispersion;
[0131] S2. Weigh 20 mg of a Pt / C catalyst having a Pt content of 40%, add 0.4 g of deionized water, 2.0 g of isopropanol and 0.2 g of the dispersion prepared in S1, and disperse the mixture under ultrasonic conditions at a power of 100 W for 60 min to obtain the catalyst slurry containing carboxyl porphyrin.
[0132] Example 6
[0133] This embodiment provides a carboxyl porphyrin-containing catalyst slurry, and the carboxyl porphyrin-containing catalyst slurry is prepared by the following steps:
[0134] S1, weighing 4.0 mg of tetracarboxylphenylporphyrin cobalt, 0.6 g of Nafion (5 wt%) resin solution (specific model: D520) and 4.0 g of isopropanol, and mixing them, and ultrasonically dispersing them at a power of 100 W for 40 min to obtain a dispersion;
[0135] S2. Weigh 20 mg of a Pt / C catalyst having a Pt content of 40%, add 0.4 g of deionized water, 2.0 g of isopropanol and 0.2 g of the dispersion prepared in S1, and disperse the mixture under ultrasonic conditions at a power of 100 W for 60 min to obtain the catalyst slurry containing carboxyl porphyrin.
[0136] Example 7
[0137] This embodiment provides a carboxyl porphyrin-containing catalyst slurry, and the carboxyl porphyrin-containing catalyst slurry is prepared by the following steps:
[0138] S1, weighing 4.0 mg of dicarboxyl iron protoporphyrin, 0.6 g of Nafion (5 wt%) resin solution (specific model: D520) and 4.0 g of isopropanol, and mixing them, and ultrasonically dispersing them at a power of 100 W for 40 min to obtain a dispersion;
[0139] S2. Weigh 20 mg of a Pt / C catalyst having a Pt content of 40%, add 0.4 g of deionized water, 2.0 g of isopropanol and 0.2 g of the dispersion prepared in S1, and disperse the mixture under ultrasonic conditions at a power of 100 W for 60 min to obtain the catalyst slurry containing carboxyl porphyrin.
[0140] Example 8
[0141] This embodiment provides a carboxyl porphyrin-containing catalyst slurry, and the carboxyl porphyrin-containing catalyst slurry is prepared by the following steps:
[0142] S1, weighing 4.0 mg of dicarboxyferrous protoporphyrin, 0.6 g of Nafion (5 wt%) resin solution (specific model: D520) and 4.0 g of isopropanol, and mixing them, and ultrasonically dispersing them at a power of 100 W for 40 min to obtain a dispersion;
[0143] S2. Weigh 20 mg of a Pt / C catalyst having a Pt content of 40%, add 0.4 g of deionized water, 2.0 g of isopropanol and 0.2 g of the dispersion prepared in S1, and disperse the mixture under ultrasonic conditions at a power of 100 W for 60 min to obtain the catalyst slurry containing carboxyl porphyrin.
[0144] Example 9
[0145] This embodiment provides a carboxyl porphyrin-containing catalyst slurry, and the carboxyl porphyrin-containing catalyst slurry is prepared by the following steps:
[0146] S1, weighing 4.0 mg of dicarboxy cobalt protoporphyrin, 0.6 g of Nafion (5 wt%) resin solution (specific model: D520) and 4.0 g of isopropanol, and mixing them, and ultrasonically dispersing them at a power of 100 W for 40 min to obtain a dispersion;
[0147] S2. Weigh 20 mg of a Pt / C catalyst having a Pt content of 40%, add 0.4 g of deionized water, 2.0 g of isopropanol and 0.2 g of the dispersion prepared in S1, and disperse the mixture under ultrasonic conditions at a power of 100 W for 60 min to obtain the catalyst slurry containing carboxyl porphyrin.
[0148] Example 10
[0149] This embodiment provides a carboxyl porphyrin-containing catalyst slurry, and the carboxyl porphyrin-containing catalyst slurry is prepared by the following steps:
[0150] S1, weighing 4.0 mg of dicarboxy nickel protoporphyrin, 0.6 g of Nafion (5 wt%) resin solution (specific model: D520) and 4.0 g of isopropanol, and mixing them, and ultrasonically dispersing them at a power of 100 W for 40 min to obtain a dispersion;
[0151] S2. Weigh 20 mg of a Pt / C catalyst having a Pt content of 40%, add 0.4 g of deionized water, 2.0 g of isopropanol and 0.2 g of the dispersion prepared in S1, and disperse the mixture under ultrasonic conditions at a power of 100 W for 60 min to obtain the catalyst slurry containing carboxyl porphyrin.
[0152] Embodiment 11
[0153] This embodiment provides a carboxyl porphyrin-containing catalyst slurry, and the carboxyl porphyrin-containing catalyst slurry is prepared by the following steps:
[0154] S1, weighing 4.0 mg of dicarboxy zinc protoporphyrin, 0.6 g of Nafion (5 wt%) resin solution (specific model: D520) and 4.0 g of isopropanol, and mixing them, and ultrasonically dispersing them at a power of 100 W for 40 min to obtain a dispersion;
[0155] S2. Weigh 20 mg of a Pt / C catalyst having a Pt content of 40%, add 0.4 g of deionized water, 2.0 g of isopropanol and 0.2 g of the dispersion prepared in S1, and disperse the mixture under ultrasonic conditions at a power of 100 W for 60 min to obtain the catalyst slurry containing carboxyl porphyrin.
[0156] Example 12
[0157] This embodiment provides a carboxyl porphyrin-containing catalyst slurry, and the carboxyl porphyrin-containing catalyst slurry is prepared by the following steps:
[0158] S1, weighing 4.0 mg of dicarboxy copper protoporphyrin, 0.6 g of Nafion (5 wt%) resin solution (specific model: D520) and 4.0 g of isopropanol, and mixing them, and ultrasonically dispersing them at a power of 100 W for 40 min to obtain a dispersion;
[0159] S2. Weigh 20 mg of a Pt / C catalyst having a Pt content of 40%, add 0.4 g of deionized water, 2.0 g of isopropanol and 0.2 g of the dispersion prepared in S1, and disperse the mixture under ultrasonic conditions at a power of 100 W for 60 min to obtain the catalyst slurry containing carboxyl porphyrin.
[0160] Embodiment 13
[0161] This embodiment provides a carboxyl porphyrin-containing catalyst slurry, and the carboxyl porphyrin-containing catalyst slurry is prepared by the following steps:
[0162] S1, weighing 4.0 mg of dicarboxyferrous protoporphyrin, 0.6 g of Nafion (5 wt%) resin solution (specific model: D520) and 4.0 g of isopropanol, and mixing them, and ultrasonically dispersing them at a power of 100 W for 40 min to obtain a dispersion;
[0163] S2. Weigh 20 mg of a PtCo / C catalyst having a Pt content of 48.4% and a Co content of 4.4%, add 0.4 g of deionized water, 2.0 g of isopropanol and 0.2 g of the dispersion prepared in S1, and ultrasonically disperse for 60 min at a power of 100 W to obtain the catalyst slurry containing carboxyl porphyrin.
[0164] Embodiment 14
[0165] This embodiment provides a carboxyl porphyrin-containing catalyst slurry, and the carboxyl porphyrin-containing catalyst slurry is prepared by the following steps:
[0166] S1, weighing 4.0 mg of dicarboxyferrous protoporphyrin, 0.6 g of Nafion (5 wt%) resin solution (specific model: D520) and 4.0 g of isopropanol, and mixing them, and ultrasonically dispersing them at a power of 100 W for 40 min to obtain a dispersion;
[0167] S2. Weigh 20 mg of PtFe / C catalyst with a Pt content of 48.4% and an Fe content of 4.4%, add 0.4 g of deionized water, 2.0 g of isopropanol and 0.2 g of the dispersion prepared in S1, and ultrasonically disperse at a power of 100 W for 60 min to obtain the catalyst slurry containing carboxyl porphyrin.
[0168] Embodiment 15
[0169] This embodiment provides a carboxyl porphyrin-containing catalyst slurry, and the carboxyl porphyrin-containing catalyst slurry is prepared by the following steps:
[0170] S1, weighing 4.0 mg of tetracarboxylphenylporphyrin, 0.6 g of Nafion (5 wt%) resin solution (specific model: D520) and 4.0 g of isopropanol, and mixing them, and ultrasonically dispersing them at a power of 100 W for 40 min to obtain a dispersion;
[0171] S2. Weigh 20 mg of a Pt / C catalyst having a Pt content of 40%, add 0.4 g of deionized water, 2.0 g of isopropanol and 0.2 g of the dispersion prepared in S1, and disperse the mixture under ultrasonic conditions at a power of 100 W for 60 min to obtain the catalyst slurry containing carboxyl porphyrin.
[0172] Comparative Example 1
[0173] This comparative example provides a catalyst slurry, which is prepared by the following steps:
[0174] 20 mg of 40 wt % Pt / C catalyst, 0.12 g of Nafion (5 wt %) resin solution, 0.4 g of deionized water and 2.0 g of isopropanol were weighed, mixed and ultrasonicated for 60 min to obtain slurry.
[0175] Comparative Example 2
[0176] This comparative example provides a catalyst slurry, which is prepared by the following steps:
[0177] S1, weigh 4.0 mg of tetraphenylporphyrin iron and 4.0 g of isopropanol, and ultrasonicate for 40 min to obtain a uniform dispersion;
[0178] S2. Weigh 20 mg of Pt / C catalyst with a Pt content of 40%, add 0.12 g of Nafion (5 wt%) resin solution and 0.4 g of deionized water, 2.0 g of isopropanol and 0.2 g of the uniform dispersion prepared in S1, and obtain a slurry after ultrasonic treatment for 60 min.
[0179] Test Case
[0180] Test samples: catalyst slurries provided in Examples 1 to 15, and catalyst slurries provided in Comparative Examples 1 to 2;
[0181] Test method:
[0182] I. Catalyst spraying on the proton exchange membrane to form a catalyst coated proton membrane module (CCM) and membrane electrode assembly:
[0183] The above catalyst slurry samples were sprayed on one side of the cathode, and then the anode catalyst slurry was sprayed on the other side, and then heated and dried. The Pt loading of the cathode and anode was 0.1 mg cm -2 The obtained CCM was assembled by sandwiching it between two pieces of carbon paper. The anode catalyst slurry was prepared according to the following method: 20 mg of 40 wt% Pt / C catalyst, 0.12 g of Nafion (5 wt%) resin solution, 0.4 g of deionized water and 2.0 g of isopropanol were weighed, mixed and ultrasonicated for 60 min to obtain the anode catalyst slurry.
[0184] II. The membrane electrode assembly obtained in I above is loaded into a fuel cell fixture for performance testing, and a single cell test is performed using Scriber's 850e fuel cell test system, specifically including the following steps:
[0185] (1) Hydrogen-oxygen polarization curve acquisition: The battery temperature was set to 80°C, the cathode and anode reaction gases were oxygen and hydrogen, the flow rate was 1000 sccm / 1000 sccm, the gas inlet pressure was 100 kPa / 100 kPa, and the cathode and anode humidity were both 100% RH.
[0186] (2) Mass activity test: The cell temperature was set to 80°C, the cathode and anode reaction gases were oxygen and hydrogen, the flow rate was 1000 sccm / 1000 sccm, the gas inlet pressure was 100 kPa / 100 kPa, and the cathode and anode humidity were both 100% RH.
[0187] (3) Electrochemical impedance spectroscopy test: using a constant potential instrument at 5A cm -2 The electrochemical impedance spectroscopy test of the single cell was carried out under current. The test conditions were: the temperature of the single cell was 80°C, the cathode and anode reaction gases were oxygen and hydrogen, the cathode and anode gas flow rates were 500sccm / 500sccm, the gas inlet pressures were 100kPa / 100kPa, and the cathode and anode humidity were both 100%RH.
[0188] (4) Conductivity test: The in-plane proton conductivity (σ) of the GORE membrane and the cofactor-modified GORE membrane was measured by EIS using a VersaSTAT 3F electrochemical workstation with a four-electrode impedance spectrometer (0.1 Hz to 0.2 MHz). The measurement was performed in ultrapure water, and the ohmic impedance (R, kΩ) was recorded in 10°C intervals from 50°C to 80°C.
[0189] The calculation formula of the membrane's in-plane proton conductivity is: σ = l / (d × × R f ), where the membrane proton conductivity (σ) is determined by the resistance (R f ), l represents the length of the tooth (1 cm), and d represents the thickness and width of the GORE membrane (1 cm).
[0190] The Arrhenius equation is used to calculate the activation energy Ea: ln(σT) = lnB-Ea / RT, where R is the Boltzmann constant, B is the pre-factor, and T is the temperature.
[0191] (5) In-situ infrared test: Electrochemical in-situ infrared was performed on an ECIR-Ⅱ in-situ cell, which was installed on a Pike VeemaxⅢATR and equipped with a MCTA detector with a germanium prism window. The data was recorded by a Thermo Nicolet Nexus 670 spectrometer. Before the test, the sample was degassed with nitrogen for 30 minutes and data was collected at 0.3V. The sample was then degassed with O2 for 30 minutes to obtain data at different potentials before the test, and O2 was continuously pumped to ensure that the electrolyte was saturated with O2. Before the test, the background spectrum of the catalyst electrode was collected at an open circuit voltage.
[0192] (6) Cyclic voltammetry: The CV curve was obtained in the potential range of 0.1 V to 1.2 V vs. RHE with a scan rate of 50 mV·s -1The CV test conditions are: the flow rate of pure H2 and pure N2 gas is 500 mL min -1 , the back pressure is 50kPa.
[0193] (7) Dry proton accessibility test: The accessibility of dry protons to Pt sites was determined by dividing the ECSA at 20% RH by the ECSA at 100% RH.
[0194] The specific test results are shown in Table 1 below:
[0195] Table 1
[0196]
[0197] As shown in Table 1, the preparation of the fuel cell catalyst assisted by the carboxyl metal porphyrin provided by the present invention achieves a double-effect synergistic effect. The metal center in the metal porphyrin can enhance the catalytic activity of the catalyst by strongly adsorbing oxygen. In addition, starting from regulating the interaction between the catalyst and the surface of the perfluorosulfonic acid electrolyte and enhancing the proton conductivity, by adding carboxyl metal porphyrin to interact with the perfluorosulfonic acid electrolyte, the active site poisoning is reduced and the proton transport of the catalyst layer is improved.
[0198] In addition, the experimental results of the present invention are shown in the following figure:
[0199] Figure 1 This is a scanning electron microscope image of the catalyst layer formed by the catalyst slurry containing carboxyl porphyrin provided in Example 8. Figure 2 This is a scanning electron microscope image of the catalyst layer formed by the catalyst slurry provided in Comparative Example 1. Figure 1 and Figure 2 It can be seen from the comparison that the catalyst layer formed by the slurry of the present invention is more sparse.
[0200] Figure 3 The polarization curve and power density curve comparison of the fuel cell containing the catalyst layer formed by the catalyst slurry of Example 8 and Comparative Example 1. It can be seen from the figure that compared with Comparative Example 1, the power density of Example 8 is significantly improved (from 1.75 W·cm -2 Increased to 2.76W·cm -2 ).
[0201] Figure 4A This is a comparison diagram of polarization curves measured for fuel cells containing membrane electrodes having catalyst layers formed by the catalyst slurries of Example 8 and Comparative Example 1. Figure 4B The mass activity comparison diagram of the fuel cell containing the membrane electrode having the catalyst layer formed by the catalyst slurry of Example 8 and Comparative Example 1. Figure 4A and Figure 4BAs shown, compared with Comparative Example 1, the mass activity of Example 8 is higher than that of Comparative Example 1, which indicates that the carboxyl metal porphyrin increases the catalyst active sites.
[0202] Figure 5 The polarization curve and power density curve comparison diagram of the fuel cell membrane electrode containing the catalyst layer formed by the catalyst slurry of Examples 5 to 8. It can be seen from the figure that the power density of Example 8 is significantly improved.
[0203] Fig. 6A The diagram is a comparison of polarization curves measured for a fuel cell containing a membrane electrode having a catalyst layer formed by the catalyst slurry of Examples 5 to 7. Figure 6B The mass activity comparison diagram of the fuel cell membrane electrode containing the catalyst layer formed by the catalyst slurry of Examples 5 to 7 is measured. Figure 4A and Figure 4B It can be seen that compared with Examples 5 to 7, Example 8 has the best mass activity, which indicates that the ferroporphyrin increases the catalyst active sites.
[0204] Figure 7 The fuel cell of the membrane electrode containing the catalyst layer formed by the catalyst slurry of Example 8 and Comparative Example 1 was subjected to 5A cm -2 Electrochemical impedance comparison diagram under . It can be seen that at this current density, the polarization of the fuel cell is mainly controlled by the oxygen transfer polarization at the catalyst / electrolyte interface, and the larger the impedance semicircle diameter, the more serious the mass transfer polarization. It can be seen from the figure that compared with Comparative Example 1, the impedance semicircle diameter of Example 8 is significantly reduced, which indicates that the carboxyl metal porphyrin effectively improves the material transfer rate inside the fuel cell at a high current density.
[0205] Figure 8 The CV curves at 20% RH and 100% RH in a fuel cell of a membrane electrode having a catalyst layer formed of the catalyst slurry of Comparative Example 1 are shown. Fig. 9 The CV curves of the fuel cell membrane electrode with the catalyst layer formed by the catalyst slurry of Example 8 at 20% RH and 100% RH. Figure 8 and Fig. 9 It can be seen from the comparison that the electrochemical active area of Example 8 is significantly larger than that of Comparative Example 1.
[0206] Fig.10 The electrochemical active area comparison diagram of the membrane electrode fuel cell of the catalyst layer formed by the catalyst slurry of Example 8 and Comparative Example 1. Fig.10 It can be seen that the proton accessibility of Example 8 is significantly greater than that of Comparative Example 1.
[0207] Fig.11The proton conductivity of the fuel cell membrane electrode having the catalyst layer formed by the catalyst slurry of Example 8 and Comparative Example 1 at 100% relative humidity and 50-80° C. It can be seen from the figure that the conductivity of Example 8 is greater than that of Comparative Example 1, proving that the carboxyl metal porphyrin in Example 8 has the effect of improving proton conductivity.
[0208] Fig.12 This is the in-situ infrared spectrum of Comparative Example 1. Fig.13 This is the in-situ infrared spectrum of Example 8. From the obtained infrared spectrum, it can be seen that the introduction of carboxyl metal porphyrin in Example 8 can quickly generate reaction intermediates to generate a large amount of water, which proves that ferrous porphyrin can accelerate the ORR kinetics.
[0209] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A catalyst slurry containing carboxyl porphyrin, characterized in that: The catalyst slurry containing carboxyl porphyrin comprises: carboxyl porphyrin compound, platinum-based catalyst, perfluorosulfonic acid electrolyte, water and alcohol.
2. The catalyst slurry containing carboxyl porphyrin according to claim 1, characterized in that, The mass ratio of the carboxyl porphyrin compound to the perfluorosulfonic acid electrolyte is 1:(1-600), preferably 1:(50-600); Preferably, the carboxyl porphyrin compound comprises any one of dicarboxy protoporphyrin, dicarboxy metal protoporphyrin, tetracarboxy phenyl porphyrin or tetracarboxy phenyl metal porphyrin or a combination of at least two thereof, preferably dicarboxy metal protoporphyrin and / or tetracarboxy phenyl metal porphyrin; Preferably, the structural formula of the dicarboxy protoporphyrin is as shown in Formula I below: Preferably, the structural formula of the dicarboxymetal protoporphyrin is as shown in Formula II below: Wherein, M is selected from any one or a combination of at least two of iron, cobalt, nickel, copper or zinc; Preferably, the structural formula of the tetracarboxyphenylporphyrin is as shown in the following formula III: Preferably, the structural formula of the tetracarboxyphenyl metalloporphyrin is as shown in the following formula IV: Wherein, M is selected from any one of iron, cobalt, nickel, copper or zinc, or a combination of at least two thereof.
3. The catalyst slurry containing carboxyl porphyrin according to claim 1, characterized in that, The platinum-based catalyst includes any one of Pt / C, PtCo / C, PtFe / C, PtNi / C or PtCu / C, or a combination of at least two thereof; Preferably, the mass percentage of platinum in the platinum-based catalyst is 10-60%.
4. The catalyst slurry containing carboxyl porphyrin according to claim 1, characterized in that, The alcohol is selected from any one of methanol, ethanol, n-propanol, isopropanol, n-butanol or tert-butanol, or a combination of at least two thereof, preferably n-propanol; Preferably, the mass ratio of the platinum-based catalyst, the carboxyl porphyrin compound, the perfluorosulfonic acid electrolyte, water and alcohol is 1:(0.01-10):(1-50):(10-100):(50-500).
5. The method for preparing a catalyst slurry containing carboxyl porphyrin according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: (1) mixing a carboxyporphyrin compound, a perfluorosulfonic acid electrolyte and an alcohol, and dispersing the mixture once to obtain a dispersion; (2) The platinum-based catalyst, water, alcohol and dispersion liquid are mixed and dispersed twice to obtain the catalyst slurry containing carboxyl porphyrin.
6. The method for preparing a catalyst slurry containing carboxyl porphyrin according to claim 5, characterized in that: In step (1), the mass ratio of the carboxyl porphyrin compound, the perfluorosulfonic acid electrolyte and the alcohol is 1:(1-600):(100-1000); Preferably, in step (1), the primary dispersion is ultrasonic dispersion, the power of the primary dispersion is 20 to 300 W, and the time of the primary dispersion is 20 to 60 min; Preferably, in step (2), the mass ratio of the platinum-based catalyst, water, alcohol and dispersion is 1:(10-100):(50-200):(1-10); Preferably, in step (2), the secondary dispersion is ultrasonic dispersion, the power of the secondary dispersion is 20 to 300 W, and the time of the secondary dispersion is 20 to 60 min.
7. Use of the catalyst slurry containing carboxyl porphyrin according to any one of claims 1 to 4 in the preparation of a fuel cell.
8. A cathode catalyst layer, characterized in that: The cathode catalyst layer includes a catalyst layer formed of the catalyst slurry containing carboxylporphyrin according to any one of claims 1 to 4.
9. A proton membrane module, characterized in that: The proton membrane assembly comprises: a proton exchange membrane and a cathode catalyst layer and an anode catalyst layer located on both sides of the proton exchange membrane; Wherein, the cathode catalyst layer comprises the cathode catalyst layer as claimed in claim 8.
10. A fuel cell, characterized in that: The fuel cell comprises a proton membrane assembly; Wherein, the proton membrane assembly comprises the proton membrane assembly as claimed in claim 9.